The Politics of British Defence 1979–98 - Freedman, Lawrence. author. aut Link
XI, 259 p.
Keywords: In this collection of essays, a number of which have never been published before, Lawrence Freedman provides an incisive and well-informed analysis of the past two decades of British defence policy, from Conservatives to Labour, and out of the Cold War. He addresses the major issues influencing policy, including the demands of European security, party politics, budgetary pressures and nuclear deterrence.